1990
DOI: 10.1152/ajpheart.1990.259.5.h1586
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for protein kinase C involvement in arteriolar myogenic reactivity

Abstract: Little information exists as to the cellular events that couple the myogenic contractile response of an arteriole to an acute rise in intravascular pressure. The aim of this study was to examine whether protein kinase C (PKC), which has been implicated in the contractile response to agonists, contributes to myogenic vasoconstriction of cremaster muscle arterioles. Studies were performed on anesthetized rats, enclosed in an airtight Plexiglas box, with the cremaster exteriorized into a bath containing Kreb's so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
114
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(127 citation statements)
references
References 0 publications
13
114
0
Order By: Relevance
“…PKCα was upregulated by approximately 50% (P < 0.01) in G αi2 -IP cells but unchanged in G αi2 -OE cells ( Figure 6B). Given that PKCα has been demonstrated to sensitize smooth muscle to contraction (12)(13)(14)(15), this upregulation in the G αi2 -IP cells is consistent with the hyperresponsive contractile phenotype. Less is known about the other PKC isoforms in regards to G protein-coupled receptor-mediated smooth muscle contraction.…”
Section: Figurementioning
confidence: 53%
See 1 more Smart Citation
“…PKCα was upregulated by approximately 50% (P < 0.01) in G αi2 -IP cells but unchanged in G αi2 -OE cells ( Figure 6B). Given that PKCα has been demonstrated to sensitize smooth muscle to contraction (12)(13)(14)(15), this upregulation in the G αi2 -IP cells is consistent with the hyperresponsive contractile phenotype. Less is known about the other PKC isoforms in regards to G protein-coupled receptor-mediated smooth muscle contraction.…”
Section: Figurementioning
confidence: 53%
“…In a positive feedback loop, PKCα sensitizes smooth muscle to receptor-mediated contraction via G q receptors. This effect has been particularly well documented in vascular smooth muscle, where PKC increases the myofilament force sensitivity to intracellular Ca 2+ concentration (12)(13)(14)(15). Interestingly, increased G αi has been reported in many animal models of cardiac hypertrophy and heart failure (18)(19)(20) as well as in human heart failure (21).…”
Section: Figurementioning
confidence: 88%
“…One attractive candidate is PKC, because several studies have found that PKC inhibitors block MT in cerebral arteries 24 and skeletal muscle arterioles. 25 Recently, Koller's laboratory reported that p38 and ERK1/2 MAP kinase inhibitors are partially involved in pressure-induced MT in rat skeletal muscle arterioles. 26 Conversely, Spurrel et al 27 have shown that ERK1/2 phosphorylation is apparently dissociated from the mechanisms directly contributing to the acute myogenic contractile response.…”
Section: Discussionmentioning
confidence: 99%
“…20-hydroxyeicosatetraenoic acid; cytochrome P-450 4A; ion channels; membrane potential STEPWISE INCREASE OF transmural pressure in isolated and cannulated cerebral arteries gives rise to a series of signaling events that culminate in stepwise constriction of the arterial segments. These arterial muscle signaling events include membrane depolarization, reduction in outward K ϩ current, increase in inward Ca 2ϩ current (via L-type Ca 2ϩ channels), translocation of PKC and phosphorylation, and elevation of inositol 1,4,5-trisphosphate and diacylglycerol, all of which are related to the activation of arterial muscle and allow arterial diameter to track changes in blood pressure, thereby maintaining blood flow relatively constant (3, 5,19,25,(27)(28)(29)(30)(31)44). The signaling pathway mediating these events involves the production of the potent vasoconstrictor 20-hydroxyeicosatetraenoic acid (20-HETE) (15,21,23,26,34).…”
mentioning
confidence: 99%